PARTISIPASI MASYARAKAT DALAM MENINGKATKAN MUTU PENDIDIKAN DI MI NW TANAK MIRA WANASABA LAUK - Hully; Lale Yaqutunnafis (KOLONI, 2022)
This paper aims to find out the participation of the community in achieving the quality of education at MI NW Tanak Mira Wanasaba Lauk. The research method used is qualitative research. There are two sources of data in this research, namely primary data obtained directly from informants and secondary data obtained from books relevant to the problem under study. Data collection techniques are carried out by observation, interviews and documentation. Data analysis is carried out logically and systematically with four stages, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The validity of the data is carried out in four ways, namely the extension of participation, the persistence of observations, the adequacy of references and triangulation. The results of this study show that the form of community participation in achieving the quality of education at MI NW Tanak Mira Wanasaba Lauk is quite diverse, including community participation in the form of finance or this material such as assistance in the form of money and donations in the form of zakat, infaq and sadakah voluntarily carried out by the community and parents of students, community participation is also in the form of ideas, thoughts, opinions and ideas, community participation in the form of decision-making. The quality of education at MI NW Tanak Mira Wanasaba Lauk cannot be separated from various programs or activities carried out in madrasahs starting from planning, implementing and evaluating school programs or activities The quality of education at MI NW Tanak Mira Wanasaba Lauk can be seen and proven by the level of class increase, which is 100% upscale in the 2020/2021 learning year and the teacher has an average undergraduate education and strengthening inculturation, namely the financing of religious values (religious culture) in the madrasa environment which is carried out every day by all elements in the madrasa environment. Keywords: Participation, Community, Quality, Education